Pendidik Dan Peserta Didik, Dalam Pendidikan Islam - Wahyudi, Muhammad; Putri, Dhea Melati; Warda, Mutia Alamiah (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
This article explores the roles of educators and learners from the perspective of Islamic education, which is central to the learning process grounded in Islamic values. In Islam, educators function not only as instructors but also as mentors, role models, and agents of change aiming to shape insan kamil (a complete and virtuous individual). On the other hand, learners are not merely recipients of knowledge but active individuals who seek, comprehend, and apply knowledge to achieve happiness in both this world and the hereafter. This study highlights the ideal characteristics of educators and learners in Islam, such as integrity, noble character, and commitment to religious teachings. Using a conceptual approach, the article emphasizes the importance of a harmonious relationship between the two in creating a holistic and transformative educational process. These findings are relevant for building an Islamic education system that positively contributes to individual and societal development.